ANTIOXIDANT AND ANTIULCER ACTIVITY OF ABRUS PRECATORIUS LEAF EXTRACT AGAINST ACETIC ACID-INDUCED GASTRIC ULCER IN RATS - LALITA NAGDA; CHANDRA PRAKASH JOSHI; JYOTI MENARIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study deals with the study of antiulcer activity of Abrus precatorius leaf extract in acetic acid-induced gastric ulcers was studied in rats. Methods: In the present study, A. precatorius leaf extract was carried out in antiulcer activity against acetic acid-induced gastric ulcer in rats. A. precatorius at doses of 150 mg/kg and 300 mg/kg were administered orally once daily for 10 days. Results: It was found that extract significantly reduced ulcer index. The plant leaves made gastric anti-secretory effect by decreasing gastric volume and acidity. Then, gastric mucin was increased, which showed gastric cytoprotective effect. The plant showed the prevention effect of increased lipid peroxidation during ulceration by acetic acid. Activities of the antioxidant enzymes were enhanced during ulceration by this plant leaves. Conclusion: Leaves of A. precatorius Linn. could decrease acetic acid-induced gastric ulcers in rats and this antiulcerogenic activity was mediated through antioxidant defense mechanism.